Transformasi Pendidikan Islam di Era Digital: Strategi Pengembangan Pesantren Berbasis Finansial Teknologi - Abu Tohir; Rina Mida Hayati; Subandi Subandi (Bustanul Ulum Journal of Islamic Education, 2024)
The financial governance of Islamic boarding schools (pesantren) in Indonesia remains predominantly manual and donor-dependent, despite their historical significance as the nation's oldest Islamic education institutions. This structural vulnerability necessitates a digital transformation to enhance institutional efficiency, accountability, and economic self-reliance. This study aims to analyze the digital financing management model as a strategic mechanism for achieving such autonomy. Employing a qualitative multiple-case study design, this research investigates several pesantren in Lampung Province that have actively adopted digital financial systems. Data were triangulated through semi-structured in-depth interviews with pesantren leaders, financial administrators, and business unit managers, complemented by participatory observation and systematic documentation of the digital platforms. The findings delineate a four-pillar implementation architecture: (1) application-based digitization of financial recording and reporting; (2) integration of electronic payment systems to streamline transactions involving students (santri) and the surrounding community; (3) development of digitally-enabled pesantren-affiliated entrepreneurial units; and (4) systematic enhancement of digital financial literacy among both administrators and students. Enabling factors include robust leadership commitment, strategic partnerships with Islamic financial institutions and fintech operators, and adequate technological infrastructure. Conversely, critical barriers persist, encompassing limited internet accessibility, low digital proficiency, and entrenched organizational resistance to systemic change. This study concludes that an integrated and sustainable digital financing model is instrumental in fostering economic independence, while simultaneously enhancing fiscal transparency and accountability in strict adherence to Sharia principles. The findings offer theoretical contributions to the discourse on digital transformation within faith-based educational institutions and provide actionable insights for policymakers seeking to modernize the financial ecosystems of traditional Islamic boarding schools.